PENATAAN TATA INFORMASI SEBAGAI PENANDA VISUAL KAWASAN DI KORIDOR JAMIN GINTING PANCUR BATU - Nasruddin; Beny O.Y Marpaung (Jurnal Koridor, 2018)
The existence of signage system is an identity and marker of area. The signage system in Jamin Ginting Street, Pancur Batu was chaotic and irregular. Jamin Ginting Street, Pancur Batu was located in Deli Serdang District, North Sumatera Province. This area was known as trade and service area. The lack of signage system arrangement guidance creates Jamin Ginting Street, Pancur Batu area was looked irregularly, slums, and distracting visually. The purpose of research is to produce signage system arrangement guideline so that create area more well organized, informative, and as marker area. This research took study about information arrangement, signage placement, street guide, advertisementand information media. The research was used qualitative descriptive analysis method. The expectation of this paper is to produce signage system arrangement guideline so therefore can improvethe identity of area and generating a visual arrangement. In conclusion,with well arrangement of signage system will improve visual aesthetic of building and area.With the appropriate of arrangement, information will be delivered more effective.